2020
DOI: 10.1002/solr.202000390
|View full text |Cite
|
Sign up to set email alerts
|

Europium (II)‐Doped All‐Inorganic CsPbBr3 Perovskite Solar Cells with Carbon Electrodes

Abstract: All‐inorganic perovskite of CsPbBr3 thin‐films solar cells has attracted increasing interest in recent years due to its potential long‐term stability over the generally used hybrid perovskites. Herein, all‐inorganic CsPbBr3 perovskites are doped with Eu2+ to enhance the efficiency of perovskite solar cells (PVSCs). The perovskite films exhibit a better crystallinity with smooth morphology after the introduction of rare‐earth elements. Hence, the hole‐transport layer‐free device with presence of Eu2+ and low‐co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Hence, the PCE improved from 5.66 to 7.28% with a higher V OC of 1.45 V through an optimized concentration of dopant of Eu 2+ under one sun of illumination. In addition, the measurements about storage stability possessed superior performances of PCE with an absence of encapsulation in air atmosphere with an RH of 70–80% …”
Section: Lanthanide Ions Doped In Pvscsmentioning
confidence: 97%
See 2 more Smart Citations
“…Hence, the PCE improved from 5.66 to 7.28% with a higher V OC of 1.45 V through an optimized concentration of dopant of Eu 2+ under one sun of illumination. In addition, the measurements about storage stability possessed superior performances of PCE with an absence of encapsulation in air atmosphere with an RH of 70–80% …”
Section: Lanthanide Ions Doped In Pvscsmentioning
confidence: 97%
“…Kumar et al reported all-inorganic HTL-free CsPbBr 3 perovskites by doping with Eu 2+ to enhance the efficiency and stability of PVSCs. 114 It is well-known that Eu ion exists in Eu 2+ or Eu 3+ states in various host materials, and the Eu 2+ type of doping offered a broader emission from 4f 6 5d 1 → 4f 7 as a parity allowed transition, which presented a wider emission in blue−green−yellow or red band regions. Meanwhile, the Eu 3+ doping obtained a luminescence that originated from its transition of 4f 6 → 4f 6 consisting of sharp lines in the region of red.…”
Section: ■ Lanthanide Ions Doped In Pvscsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,24,25 Other reports have found limited uptake of homovalent B-site cations (i.e., with a 2+ charge) other than tin into a lead halide perovskite, resulting in only weak band gap tuning. [26][27][28][29][30][31] It was found that when the precursor solutions have a B-site dopant concentration of less than 1 mol percent, then the dopant B-site cation will be incorporated into the parent lead halide perovskite. At higher doping concentrations, however, a secondary phase containing a higher concentration of dopant is formed at the surface.…”
Section: Straus and Cavamentioning
confidence: 99%
“…In addition to OLHPs, RE ions are also incorporated into all-inorganic perovskites to improve the film quality and applied to PSCs. [34,131,134] Incorporating the Eu 3+ into CsPbI 3 to prevents the black to the yellow phase (δ-CsPbI 3 ) transformation was reported by Miyasaka's group. [135] The incorporating of Eu 3+ can suppress the dark current, increase in V oc and the stability, which indicates that Eu 3+ doped into CsPbI 3 can reduce the recombination.…”
Section: All-inorganic Perovskite Solar Cellsmentioning
confidence: 99%